Addressing Anger Using Sensorimotor Psychotherapy and Cognitive Behaviour Therapy - Flynn, Sarah M. (Canadian Journal of Counselling and Psychotherapy, 2010)
A young woman initiated counselling services at a community agency to address her explosive anger that was a remnant of childhood physical and emotional abuse. Senso-rimotor psychotherapy was used to help this client learn how to monitor and regulate her sensorimotor processes. In conjunction with this approach, Cognitive behavioural therapy was used to help this client process her traumatic experiences and reframe her core beliefs about herself as a victim. This client learned how to control her anger by tracking her physiological reactions in upsetting situations and implementing adaptive techniques to relax herself.